2015
DOI: 10.3795/ksme-b.2015.39.1.061
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Flow and Oxygen Transfer Characteristics of Vertical Orifice Ejector

Abstract: The objective of this study is to experimentally investigate the mixed flow behaviors and oxygen transfer characteristics of a vertical orifice ejector. The experimental apparatus consisted of an electric motor-pump, an orifice ejector, a circulation water tank, an air compressor, a high speed camera unit and control or measurement accessories. The mass ratio was calculated using the measured primary flow rate and suction air flow rate with experimental parameters. The visualization images of vertically inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…On one hand, the enhancement of DO dissolution in the MPSR was the result of the extended residence time of the air bubbles in the slurry, which was caused by inner circulation of the bubbles in the swirl. The residence time of the bubbles was very significant for enhancing the oxygen transfer rate (Kim et al 2015). Javed also found that the gas phase mass transfer coefficient (K g a) increased when a swirl was formed in the reactor (Javed et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…On one hand, the enhancement of DO dissolution in the MPSR was the result of the extended residence time of the air bubbles in the slurry, which was caused by inner circulation of the bubbles in the swirl. The residence time of the bubbles was very significant for enhancing the oxygen transfer rate (Kim et al 2015). Javed also found that the gas phase mass transfer coefficient (K g a) increased when a swirl was formed in the reactor (Javed et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…정성적 가시화 이미지는 고속 카메라(Phantom Miro eX2)와 조명장치(ARRI)를 이용하여 초당 120프레임 (120fps)의 속도로 촬영하였으며, (2,16) 이미지 분석시스템 (17) 의 영상 이원화(binarization) 기법 ) …”
Section: 서 론unclassified
“…As the primary flow pressure increases and the mass ratio decreases, the mass transfer rate increases because of the fine bubbles and wider distribution of the bubbles. (2,16) …”
Section: 서 론mentioning
confidence: 99%